Reformed theology and politics - Van de Beek, Bram (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
The Reformed tradition has always been involved in political issues. In terms of this perspective the views of two major Reformed theologians, John Calvin and Karl Barth, are compared with opinions in early Christianity regarding the relation between Christians and politics. Theologians in the early patristic period kept their distance from politics. Calvin pleaded for sober involvement, while Barth eagerly calls for a prophetic participation in the public sphere. These differences may be interpreted as a natural development related to historical changes: from a persecuted community to the corpus christianum, and subsequently to the challenge of a perverse political ideology, and the call for a response in a new situation its defeat. From this perspective all three positions are understandable. However, being true to the Reformed call ad fontes one must conclude that Barth’s theology is totally different from both that of early Christianity and the New Testament. This calls for a reconsideration of positions regarding the relation of church and politics.